PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Ari Irawan; Debbi Chyntia Ovami; Argo Putra Prima; Arie Pratania Putri (Universitas Dharmawangsa, 2023)
ABSTRACTThis study aims to determine the effect of disclosure of Corporate Social Responsibility on Corporate Value in banking companies listed on the IDX. This research was conducted at banking companies listed on the IDX using annual reports from 2020-2022. The samples in this study were 43 companies using a purposive sampling technique, namely the samples taken according to the criteria determined by the researcher. The data used is secondary data obtained from the official website, namelywww.idx.co.id. the data analysis method used in this study is the panel regression model. Data management uses the Eviews application version 10. The results of this study are that Corporate Social Responsibility (CSR) does not have a significant effect on Company Value, this can be seen from the probability value > 0.05, namely 0.2252 and the conclusion is that Corporate Social Responsibility (CSR) ) has no significant effect on Firm Value in this case measured by tobinsq.Keywords: Corporate Social Responsibility, Corporate Values